An assessment of implementation and effectiveness of mass drug administration for prevention and control of schistosomiasis and soil-transmitted helminths in selected southern Malawi districts - Peter Makaula; Sekeleghe Amos Kayuni; Kondwani Chidzammbuyo Mamba; Grace Bongololo; Mathias Funsanani; Janelisa Musaya; Lazarus Tito Juziwelo; Peter Furu (BMC, 2022)
Abstract Background Mass drug administration (MDA) is one of the key interventions recommended by WHO for prevention and control of neglected tropical diseases (NTD). In Malawi, MDA is widely carried out annually since 2009 for prevention and control of schistosomiasis and soil-transmitted helminths (STH). No study has been carried out to assess effectiveness of the MDA approach and to document perceptions of health providers and beneficiaries regarding use of MDA. This study was done to understand how well MDA is being implemented and to identify opportunities for improvement in MDA delivery in Malawi. Methods Designed as a cross-sectional and multi-methods research, the study was carried out in three southern Malawi districts of Chiradzulu, Mangochi and Zomba. In each district, four health centres and 16 villages were randomly selected to participate. A mixed-methods approach to data collection focusing on quantitative data for coverage and knowledge, attitudes and practices assessments; and qualitative data for assessing perceptions of health providers and beneficiaries regarding MDA was used. Quantitative data were processed and analyzed using IBM SPSS software version 26 while qualitative data were analysed using NVivo 12 for Windows. Results Knowledge levels about schistosomiasis and STH in the districts varied according to disease aspects asked about. Majority are more knowledgeable about what schistosomiasis is (78%) and whether STH are treatable with drugs (97%); with least knowledgeable about the organism that transmits schistosomiasis (18%), types of schistosomiasis (11%) and what causes STH (20%). In 2018 and 2019 the districts registered high coverage rates for praziquantel and albendazole using community-based MDA (73-100%) and using school-based MDA (75-91%). Both the health authorities and community members perceived the MDA approach as good because it brings treatment closer to people. Conclusion With the high MDA coverage obtained in communities and schools, the effectiveness of MDA in the target districts is satisfactory. There are, however, several challenges including disproportionate knowledge levels, which are hampering progress towards attainment of the 2030 global NTD goals. There is a need for promotion of community participation and partnerships as well as implementation of other recommended interventions for sustainable prevention and control of schistosomiasis and STH.